On Onset of Chaotic Convection in Couple-Stress Fluids - Jawdat, Jadallah M.; Hashim, Ishak; Bhadauria, Beer S.; Momani, Shaher (Mathematical Modelling and Analysis, 2014)
The effect of couple-stress fluid field on chaotic convection in a fluid layer heated from below was studied in this paper based on the theory of dynamical systems. A low-dimensional, Lorenz-like model was obtained using Galerkin truncated approximations. The fourth-order Runge–Kutta method was employed to solve the nonlinear system. The results show that inhibition of chaotic convection depends strongly on the couple-stress parameter.